Republic of Croatia : 2011 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Croatia. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, the economic stability of Croatia is overviewed after the global crisis. The reforms outlined in the government's economic recovery program (ERP) are in progress. Judicial reforms are instituted to strengthen bankruptcy procedures for companies. To improve the medium-term growth prospects of the economy, there is a need to tackle the structural rigidities. Executive Directors agreed that monetary policy should aim at gradually building up reserves in order to increase Croatia's resilience to external vulnerabilities, while exercising caution toward shifts.